SPECIFIC TRAINING FOR NUCLEAR SERVICE PROVIDERS - Srebotnik, Rebeka; Lešnjak, Andrej (Journal of Energy Technology, 2024)
The aim of the specific training courses for nuclear service providers is to ensure that capable personnel as a paramount objective not only for nuclear power plants, research facilities, institutes and regulatory bodies, but also for industries that provide products and services in support of the maintenance and operation of existing plants, as well as for the whole supply chain for new builds. Q Techna has been systematically developing an education and training program in support of their services to nuclear power plants and facilities. Apart from locally available education and training, opportunities are taken, in cooperation with foreign companies and institutions, to gain and maintain knowledge and skills. Experience from jobs at foreign nuclear power plants complements that. For service providers, it is of crucial importance to assure a balanced mix of well-trained and educated personnel. Apart from external and internal training courses of its own personnel, Q Techna delivers training courses to other interested parties in the nuclear industry. More specifically, this paper focuses on training and certification of non-destructive testing (NDT) personnel.